Exploratory study of Cohesion in junior soccer athletes - Morao, Kauan Galvao [UNESP]; Verzani, Renato Henrique [UNESP]; Bagni, Guilherme [UNESP]; Rebustini, Flavio [UNESP]; Machado, Afonso Antonio [UNESP] (Univ Nac La Plata, Fac Humanidades & Ciencias Educ, 2019)
The study aims to investigate the cohesion in junior soccer athletes. We analysed 162 athletes who participated in Copa Sao Paulo. To evaluate cohesion, we used the Questionario de Ambiente de Grupo (QAG). For the statistics analysis, descriptive analysis, multivariate analysis of variance (MANOVA) and ANOVA to repeated measures were conducted, both with Bonferroni' post hoc test. The results pointed out levels of cohesion above the expected average in dimensions such as individual attraction and to group and the higher incidence of important statically results were founded in comparison with game position. It might be possible to indicate that the differences between the cohesion levels are more present when we analyse the game position, rather than the age, education level and time of practice. Therefore, cohesion is more focused in group dynamics than in athletes' individual characteristics.
Keywords: Group Cohesion; Soccer; Sport psychology